Предмет: Алгебра,
автор: Fox1111Live
Упростите выражение:
Приложения:
![](https://files.topotvet.com/i/983/983111617a20106726305d10113bafbb.jpg)
Ответы
Автор ответа:
1
(a+7)(a-1)+(a-3)^2
(a+7)(a-1)=a^2+7a-a-7=a^2 +6a -7
(a-3)^2 = a^2 - 6a + 9
a^2 + 6a -7 + a^2 - 6a + 9 = 2a^2 +2
(a+7)(a-1)=a^2+7a-a-7=a^2 +6a -7
(a-3)^2 = a^2 - 6a + 9
a^2 + 6a -7 + a^2 - 6a + 9 = 2a^2 +2
Fox1111Live:
^2 это степень?
Похожие вопросы
Предмет: Геометрия,
автор: catherinedmitrievna
Предмет: Экономика,
автор: sjsudg638
Предмет: Математика,
автор: asarajmanov
Предмет: Алгебра,
автор: CelldwellerSyb